L‐Lactate mediates neuroprotection against ischaemia by increasing TREK1 channel expression in rat hippocampal astrocytes in vitro. Issue 2 (26th May 2016) - Banerjee, Aditi; Ghatak, Swagata; Sikdar, Sujit Kumar
Abstract: Brain ischaemia is a highly debilitating condition where shortage of oxygen and glucose leads to profuse cell death. Lactate is a neuroprotective metabolite whose concentrations increase up to 15–30 mmol/L during ischaemia and TREK1 is a neuroprotective potassium channel which is upregulated during ischaemia. The aim of this study was to investigate the effect ofl ‐lactate on TREK1 expression and to evaluate the role ofl ‐lactate‐TREK1 interaction in conferring neuroprotection in ischaemia‐prone hippocampus. We show that 15–30 mmol/Ll ‐lactate increases functional TREK1 protein expression by 1.5–3‐fold in hippocampal astrocytes using immunostaining and electrophysiology. Studies with transcription blocker actinomycin‐D and quantitative PCR indicate that the increase in TREK1 expression is due to enhanced TREK1 mRNA transcription. We further report thatl ‐lactate‐mediated increase in TREK1 expression is via protein kinase A (PKA)‐dependent pathway. This is the first report of an ischaemic metabolite affecting functional expression of an ion channel. Our studies in an in vitro model of ischaemia using oxygen glucose deprivation show that 30 mmol/Ll ‐lactate fails to reduce cell death in rat hippocampal slices treated with TREK1 blockers, PKA inhibitors and gliotoxin. The above effects were specific tol ‐lactate as pyruvate failed to increase TREK1 expression and reduce cell death.l ‐Lactate‐induced TREK1 upregulation is a novel finding of physiological significance as TREK1 channels contribute to neuroprotection by enhancing potassium buffering and glutamate clearance capacity of astrocytes. We propose thatl ‐lactate promotes neuronal survival in hippocampus by increasing TREK1 channel expression via PKA pathway in astrocytes during ischaemia. Insufficient blood supply to the brain leads to cerebral ischaemia and increase in extracellular lactate concentrations. We incubated hippocampal astrocytes in lactate and observed increase in TREK1 channel expression via protein kinase A (PKA). Inhibition of TREK1, PKA and metabolic impairment of astrocytes prevented lactate from reducing cell death in ischaemic hippocampus. This pathway serves as an alternate mechanism of neuroprotection. Cover image for this issue: doi:10.1111/jnc.13326 . Abstract : Insufficient blood supply to the brain leads to cerebral ischaemia and increase in extracellular lactate concentrations. We incubated hippocampal astrocytes in lactate and observed increase in TREK1 channel expression via protein kinase A (PKA). Inhibition of TREK1, PKA and metabolic impairment of astrocytes prevented lactate from reducing cell death in ischaemic hippocampus. This pathway serves as an alternate mechanism of neuroprotection. Cover image for this issue: doi:10.1111/jnc.13326 .